2019
DOI: 10.5430/ijfr.v10n2p68
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants of Profitability of the Pharmaceutical Industry of Bangladesh: A Random Effect Analysis

Abstract: The present study investigates the factors affecting the profitability of the pharmaceutical industry of Bangladesh. Using the data of 20 listed pharmaceutical companies fully functional in Bangladesh, we found both the firm specific and the macroeconomic specific variables affect the profitability of the companies. A panel dataset of 10 years starting from 2007 to 2016, we ran the random effect regression. The regression output depicts that among the firm specific variables, sales, operating income, operating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…Positive relationship was confirmed by Lee [22] and Pervan et al [32]. Despite these findings, Islam and Khan [40] found that the sales to total asset ratio had a negative effect on the company profitability.…”
Section: Methodsmentioning
confidence: 81%
See 3 more Smart Citations
“…Positive relationship was confirmed by Lee [22] and Pervan et al [32]. Despite these findings, Islam and Khan [40] found that the sales to total asset ratio had a negative effect on the company profitability.…”
Section: Methodsmentioning
confidence: 81%
“…The positive growth -profitability relationship shows that the level of profitability is higher in companies where growth in sales has been noticed [31]. Asimakopoulos et al [19] suggested Goddard et al [27]; Maçãs Nunes et al [34]; Serrasqueiro [15]; Eriotis et al [38]; Doğan [39]; Al-Jafari and Al Samman, [24]; Alarussi and Alhaderi [16]; Islam and Khan [40]; Agiomirgianakis et al [17] Company size measured by sales Abey and Velmurugan [31]; Alarussi and Alhaderi [16]; Asimakopoulos et al [19]; Doğan [39]; Al-Jafari and Al Samman [24]; Pratheepan [25]; Banchuenvijit [20]; Serrasqueiro [15]; Bhutta and Hasan [26]; Denčić-Mihajlov [36] Agiomirgianakis et al [17]; Abu-Tapanjeh [18]; Dhawan [37] Company size measured by assets Multifactor regression analysis Goddard et al [27] Panel data model Maçãs Nunes et al [34] Dynamic Panel data model Serrasqueiro [15] Dynamic Panel data model Eriotis et al [38] Ordinary Least Square Regression Doğan [39] Multiple Regression Analysis Al-Jafari and Al Samman [24] Panel Ordinary Least Squares model Alarussi and Alhaderi [16] Pooled Ordinary Least Squares Regression Islam and Khan [40] Random-effects Panel data model Agiomirgianakis et al [17] Panel EGLS (Cross-section weights) method Boadi et al [13] Ordinary Least Square Regression Tapanjeh [18] Regression analysis Dhawan [37] Fixed-effects Panel data model Abey and Velmurugan [31]...…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The number of studies on modelling a firm's profitability has increased in recent years (e.g., Hirsch and Schiefer, 2016;Lee and Alnahedh, 2016;Hongwei et al, 2017;Islam and Khan, 2019). Some of them focused on cultural/religion-oriented markets from consumer perspective (Aisyah, 2017;Mustafar et al, 2018;Nawawi, Roslin and Hamid, 2018;Shahid, Ahmed and Hasan, 2018;Sriminarti and Nora, 2018;Putri, Daryanti and Ningtias, 2019).…”
Section: Introductionmentioning
confidence: 99%